2012
DOI: 10.1016/j.healthplace.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Does non-employment contribute to the health disadvantage among lone mothers in Britain, Italy and Sweden? Synergy effects and the meaning of family policy

Abstract: This study analyses self-rated health and non-employment and potential synergy effects among lone and couple mothers aged 25-59 in Britain, Sweden and Italy, representing different family policy categories using data from national surveys (2000)(2001)(2002)(2003)(2004)(2005). Synergy effects on health were calculated by synergy index. Non-employment only marginally contributed to the excess risk of poor health among lone mothers but there were synergy effects between lone motherhood and nonemployment in all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…Economic strain is increasingly associated with the worse health conditions of lone parents, even though the Swedish welfare state intervenes substantially. In follow-up comparisons between Sweden, Britain, and Italy, economic conditions turned out to be less important as a main factor to explain bad health, but the synergy between lone motherhood and non-employment turned out to be a highly important mediation factor (Burstrom et al 2010;Fritzell et al 2012;Whitehead et al 2000). The comparative study revealed influences of both policy regimes and a country's culture and tradition.…”
Section: Health Trajectoriesmentioning
confidence: 99%
“…Economic strain is increasingly associated with the worse health conditions of lone parents, even though the Swedish welfare state intervenes substantially. In follow-up comparisons between Sweden, Britain, and Italy, economic conditions turned out to be less important as a main factor to explain bad health, but the synergy between lone motherhood and non-employment turned out to be a highly important mediation factor (Burstrom et al 2010;Fritzell et al 2012;Whitehead et al 2000). The comparative study revealed influences of both policy regimes and a country's culture and tradition.…”
Section: Health Trajectoriesmentioning
confidence: 99%
“…It is likely that health benefits of paid maternity leave vary depending on the characteristics of the sample, such as marital status, ethnic background, job characteristics and socioeconomic characteristics. For example, lone mothers are consistently found to have poorer health than married or partnered mothers, and their poorer health is linked to their lower socioeconomic position (Burstrom et al, 2010;Fritzell et al, 2012;Lahelma et al, 2002). Thus, having access to paid leave at the time of birth may have greater health benefits for lone mothers.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges are further enhanced in the United States by the absence of many public social protections that enable working men and women to reduce conflicts between work and family responsibilities (Gornick & Meyers, 2003; Gornick, Meyers, & Ross, 1997; Heymann, 2000; Kelly, 2003; Kelly & Moen, 2007; King, et al, 2013). Evidence from Scandanavia suggests that extensive social policies supporting working parents have benefits for both parents and children (Burstrom et al, 2010; Fritzell et al, 2012; Whitehead, Burstrom, & Diderichsen, 2000) but may not reduce sickness absence or burnout, especially for women. Rates of sickness absence remain high in Sweden and women dominate among the long-term sick listed (Johansson, 2002; Vingard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%